Prosecution and Protection from a Gender Perspective in Trafficking of Women - Netkova, Bistra; Qosaj Mustafa, Ariana Qosaj (Advances in Social Sciences Research Journal, 2018)
This article examines trafficking in women from a human rights perspective and through the gender based lenses. Thus it concludes that prosecution and protection as preconditions for successful fight against trafficking in women lies on enacting of laws that are in line with international standards, implementation of those and successful prosecution of traffickers. Furthermore, it points out that protection of victims is an important and integral part of the process of prosecution of traffickers and that it should be based on human rights principles as stipulated in international legal instruments and jurisprudence